Main incidence trends in adolescents aged 15–17 years in Moscow, including COVID-19 pandemic - A. M. Podchernina (Здоровье мегаполиса, 2022)
Introduction. The article provides information about the disease incidence in adolescents in Moscow, the indicators of general and primary disease incidence rates including some particular disease groups, as well as the analysis of their chronicity. The article provides information about the impact of the COVID-19 pandemic on disease incidence trends in general and in some particular disease groups.Materials and methods. The data was obtained from Rosstat open data, Federal Statistical Observation Form No. 12 “On the number of diseases registered in patients residing in the provision area of a medical organization” from 2015 to 2021.Results and conclusion. Isolation of adolescents, which is the most socially active group of children, affected both particular diseases and disease groups in general. Some diseases that are not acute and do not require emergency care are presented in the statistics data for 2021, thus reflecting a certain cumulative effect. It is worth noting that the pandemic has significantly influenced the incidence of injuries, intoxication and infectious diseases. In addition to disease burden in particular disease groups, throughout the study period the chronicity rates of diseases of the musculoskeletal system and connective tissue (4.6% on average), mental diseases (4.5%), diseases of the eye and its accessory parts were quite high (4.5%) in Moscow.